Isolation of the polar and lateral flagellum-defective mutants in Vibrio alginolyticus and identification of their flagellar driving energy sources. - Kawagishi, I (1995)
Vibrio alginolyticus has two types of flagella (polar and lateral) in one cell. We isolated mutants with only a polar flagellum (Pof+ Laf-) or only lateral flagella (Pof- Laf+). Using these mutants, we demonstrated that the energy sources of the lateral and polar flagellar motors in V. alginolyticus are H+ and Na+ motive forces, respectively, as in the related species V. parahaemolyticus.